1999
DOI: 10.1016/s1095-6433(99)90367-7
|View full text |Cite
|
Sign up to set email alerts
|

A novel neuropeptide, Hym-355, positively regulates neuron differentiation in Hydra

Abstract: During the course of a systematic screening of peptide signaling molecules in Hydra a novel peptide, Hym-355 (FPQSFLPRG-NH2), was identified. A cDNA encoding the peptide was isolated and characterized. Using both in situ hybridization and immunohistochemistry, Hym-355 was shown to be expressed in neurons and hence is a neuropeptide. The peptide was shown to specifically enhance neuron differentiation throughout the animal by inducing interstitial cells to enter the neuron pathway.Further, co-treatment with a P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
82
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(85 citation statements)
references
References 56 publications
3
82
0
Order By: Relevance
“…In this context, it is interesting to note that many of these epithelial cell-specific genes are involved in intracellular signaling and signal transduction. Another example of such signaling is the release from epithelial cells of peptide signals regulating nerve cell differentiation (37). Both observations are consistent with the idea that, in multicellular animals, there is cross talk between different cell lineages to maintain constant proportions.…”
supporting
confidence: 68%
See 1 more Smart Citation
“…In this context, it is interesting to note that many of these epithelial cell-specific genes are involved in intracellular signaling and signal transduction. Another example of such signaling is the release from epithelial cells of peptide signals regulating nerve cell differentiation (37). Both observations are consistent with the idea that, in multicellular animals, there is cross talk between different cell lineages to maintain constant proportions.…”
supporting
confidence: 68%
“…Six of them encoded neuropeptides and were expressed in ganglion cells (SI Table 5). Various neuropeptides have been isolated from Hydra by using systematic screening for peptide signaling molecules (37)(38)(39), and four sequences reported in this study encode such known neuropeptides (SI Fig. 3D).…”
mentioning
confidence: 91%
“…Hym355 appears to be involved in a positive feedback loop stabilizing the pattern of nerve cells throughout Hydra tissue. A second peptide, Hym33H (AALPW), which is synthesized by epithelial cells, counteracts the effect of Hym355 (Takahashi et al, 2000).…”
Section: Factors Regulating Nerve Cell Differentiationmentioning
confidence: 99%
“…This possibility was the motivation for the Hydra peptide project (Takahashi et al, 1997;Fujisawa, 2008), which had the goal of identifying novel peptides involved in developmental processes in Hydra (Fujisawa and Hayakawa, 2012). This project has led to the identification of the Hym-301 peptide, which is involved in head formation, Hym-355 and the PW peptides, which play stimulatory and inhibitory roles, respectively in nerve cell differentiation, and Hym-346 and Hym-323 peptides, which have roles in foot formation (Grens et al, 1999;Takahashi et al, 2000;Takahashi et al, 2005;. Although Hayakawa et al, (2007) have shown that a computational approach can be used to identify potential precursors to peptides in Hydra in ESTs or in gene models from the Hydra genome, functional screens of the sort developed by the Hydra Peptide Project clearly still have a role to play in defining the molecules that control developmental processes in Hydra, with the genome sequence playing an enabling role.…”
Section: What Genes Are Novel?mentioning
confidence: 99%